(untitled) (Konferensiyalar | Conferences, 2024)
This article delves into the multifaceted challenges faced when translating jargon from English into Uzbek. It examines the intricate interplay of cultural and linguistic differences, limited lexical resources, the dynamic nature of jargon, conceptual equivalency, and contextual considerations. Through comprehensive research, case studies, and insights from professional translators, this article offers strategies to overcome these challenges, ensuring accurate and effective translations.